PENGEMBANGAN VARIETAS TANAMAN TAHAN SALINITAS MELALUI REKAYASA GENETIK DAN MARKET ASSISTED SELECTION (MAS) - Amelia, Kiki; Hasrinah; Nur Aisyah; Rachmawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Soil salinity is a major limiting factor in global agricultural production, affecting plant growth, physiology, and yield, and poses a major threat to global agricultural productivity. The accumulation of Na⁺ and Cl⁻ ions cause osmotic stress, ion toxicity, and metabolic disorders in plants. Developing salinity-tolerant crop varieties is an important strategy for increasing the productivity of marginal lands. Modern biotechnological approaches such as genetic engineering and marker-assisted selection (MAS) enable the development of superior varieties more quickly and accurately than conventional methods, offering a rapid and precise solution for developing salt-tolerant crop varieties. Genetic engineering allows the direct introduction of salinity tolerance genes, while MAS allows the selection of tolerance genes based on molecular markers. This article reviews the basic mechanisms of salinity stress, the role of tolerance-related genes, and biotechnological strategies used in plant breeding. An integrative approach between genetic engineering and MAS is an effective strategy for producing varieties adaptive to saline soils in modern plant breeding (Munns & Tester, 2008; Flowers & Colmer, 2015).